Corals from the Upper Cretaceous (Maastrichtian) Ocozocoautla Formation, Chiapas, Mexico - Harry F. Filkorn; Javier Avendaño-Gil; Marco A. Coutiño-José; Francisco J. Vega-Vera (Revista Mexicana de Ciencias Geológicas)
The coral species from the Upper Cretaceous (Maastrichtian) strata of the Ocozocoautla Formation in Chiapas, Mexico, are identiﬁed, described and illustrated for the ﬁrst time. This coral fauna is composed of 12 species, nine of which are colonial, presumably zooxanthellate, reef-building forms. This is the ﬁrst time that six of these species have been reported from Mexico. The majority (11) of these species are endemic to the Caribbean region and known only from the Late Cretaceous.